2018
DOI: 10.1111/bjd.16256
|View full text |Cite
|
Sign up to set email alerts
|

Use of the hCONSORT criteria as a reporting standard for herbal interventions for common dermatoses: a systematic review

Abstract: Our data indicate lack of adherence to hCONSORT extension criteria. Adherence to hCONSORT guidelines should be encouraged in order to provide high-quality reporting of research on herbal interventions in dermatology. Doing so may ease the integration of CAM into conventional medical practice and provide actionable data to providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
(67 reference statements)
0
5
1
Order By: Relevance
“…Our results are similar to the 2011 systematic review of 11 top selling herbal products in the USA (mean compliance, 38%), 7 and the 2018 review that included herbal products for acne, atopic dermatitis, or psoriasis (15% of studies reported less than half of hCONSORT items). 8 On the other hand, our findings contrast with the 2015 systematic review that reported more than 80% of included studies that complied to more than 50% of the items in the hCONSORT checklist. 9 Since this 2015 review included RCTs for 20 registered herbal products in Thailand, the high reporting compliance may be a reflection of the robust herbal medicine industry and integration into their national formulary.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results are similar to the 2011 systematic review of 11 top selling herbal products in the USA (mean compliance, 38%), 7 and the 2018 review that included herbal products for acne, atopic dermatitis, or psoriasis (15% of studies reported less than half of hCONSORT items). 8 On the other hand, our findings contrast with the 2015 systematic review that reported more than 80% of included studies that complied to more than 50% of the items in the hCONSORT checklist. 9 Since this 2015 review included RCTs for 20 registered herbal products in Thailand, the high reporting compliance may be a reflection of the robust herbal medicine industry and integration into their national formulary.…”
Section: Discussioncontrasting
confidence: 99%
“…7 None of the studies stated using a standardized herbal product, and this may be because the products used in traditional practice are not pure compounds and active constituents have not been identified. Compared to this finding, the previous systematic reviews showed that 33% 12 to 51% 7 of studies reported on standardization details. This may be explained by the more developed herbal industry in higher-income countries, and is especially relevant in resource-limited countries like the Philippines where lack of access to costly drugs may be bridged by readily available traditional medicinal plants.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations